Using Silicone Impression Material and Acrylic Resin to Fabricate Remount Casts for Removable Partial Dentures - Yung-tsung Hsu, DDS, MS1 and John B. Farmer, DMD2 (Journal of Prosthodontics, 2005)
A technique is described for fabrication of a remount cast for a removable partial denture